Association analysis of interleukin‐23 receptor SNPs and SAPHO syndrome in Chinese people. (8th November 2019) - Guo, Changlong; Li, Chen; Han, Feifei; Gao, Jianen; Ma, Xu
Abstract: Objective: SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis, and osteitis) is an autoimmune disease of unknown etiology that seriously affects patients' daily lives. Family‐based investigations support genetic contributions toward disease susceptibility. The present study evaluated whether the previously reported autoimmune disease‐associated single nucleotide polymorphisms (SNPs) have any genetic overlap with SAPHO syndrome. Method: Genomic DNA was obtained from 71 SAPHO patients and 104 healthy controls. The SNP genotypes of each patient were determined with polymerase chain reaction and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Genotype, allele, and haplotype frequencies were analyzed with SPSS software. Results: Three SNP sites (rs10889677 and rs2201841 of interleukin [IL]‐23R, and rs2243248 of IL‐4) showed significant correlation with the occurrence of SAPHO syndrome in additive and dominant genetic models, while rs7517847 of IL‐23R showed substantial correlation with SAPHO in the dominant genetic model. The G allele of rs2243248 (IL‐4) was a high risk factor for SAPHO ( P = 2.41e−5, odds ratio [OR] =7.79, 95% CI: 2.59‐23.3). The haplotype (A‐G‐C‐G‐T), comprising 5 SNPs of the IL‐23R gene, had a significantly higher frequency in the SAPHO cohort than in the controls ( P = .011, OR = 2.05, 95% CI: 1.12‐3.60). Conclusion: Variants rs10889677, rs2201841, and rs7517847 of IL‐23R, and variant rs2243248 of IL‐4, showed strong associations with SAPHO syndrome. Patients carrying the A‐G‐C‐G‐T haplotype of IL‐23 are significantly more likely to develop SAPHO syndrome.